RAS prelims sucess series (PSS-II): Economy, Geography, Reasoning & Mental Ability - Drishti (New Delhi Drishti Publications, 2023)
Drishti IAS RAS PSS-II ECONOMY, GEOGRAPHY REASONING & MENTAL ABILITY & Rajasthan state and subordinate services examination.
Keywords: Rajasthan state exam; Economy; Geography